Residential vacancy in city center: The case of S\~ao Paulo - Vanessa Gapriotti Nadalin (Institute for Applied Economic Research (ipea), 2015)
S\~ao Paulo's metropolitan area is one of the largest urban spaces in the world. As it happens with any other large metropolitan area, understanding its structure, problems and dynamics is not a simple task. The structure of cities has been studied by urban economics ever since von Thünen's land use theory was adapted to urban contexts. Research on property and housing markets have followed a related but different approach. On the one hand, housing markets have been modeled with emphasis on the specific features of properties such as durability, heterogeneity, and construction costs. On the other hand, research on real estate finance has been developing and applying a variety of valuation methods, focusing on the supply and demand adjusting mechanisms and considering properties as assets. These three areas of investigation have not always been connected in a systematic manner. Yet, we argue that there is a case for integrating them due to their intrinsic spatial dimension. In the past decades, when the S\~ao Paulo became the national manufacturing centre, it has experienced great population growth. Many problems have emerged, especially those connected with housing such as illegal slums, flophouses, informal settlements, squatting and homelessness. This significant housing deficit indicates the need to search for alternatives in the provision of good quality housing. At the same time, there is a general spatial pattern of residential vacancy: high vacancies in central areas and low vacancies in suburbs. The city centre location advantages and urban amenities are a misuse of scarce resources. This paper attempts to contribute to this debate through an empirical analysis of the determinants of residential vacancy rates in S\~ao Paulo's metropolitan area. We use a panel of census tract level data for the years 2000 and 2010 combining standard spatial econometric methods with hedonic modelling. Our results suggest that there are two main groups of determinants: one related to local characteristics of housing markets and another constituted by individual building features.
Keywords: R31; 330; vacancy rates; housing; city center; hedonic modeling